2019
DOI: 10.3390/nu11030694
|View full text |Cite
|
Sign up to set email alerts
|

Coffee Consumption and Risk of Colorectal Cancer: A Systematic Review and Meta-Analysis of Prospective Studies

Abstract: Coffee is a blend of compounds related to gastrointestinal physiology. Given its popularity and the epidemiology of colorectal cancer, the impact of this beverage on public health could be considerable. Our aim was to provide an updated synthesis of the relationship between coffee consumption and the risk of colorectal cancer. We conducted a systematic review and meta-analysis of 26 prospective studies. Regarding colorectal cancer, no significant relationship was detected. Stratifying for ethnicity, a protecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 44 publications
5
37
0
Order By: Relevance
“…Regarding ethnicity, a significant protective association was noted in European men and in Asian women. Decaffeinated coffee exhibited a protective effect in both men and women [ 53 ]. On the contrary, other researchers have found no protective evidence for coffee.…”
Section: Coffee and The Gastrointestinal Tract: Focus On The Mucosmentioning
confidence: 99%
“…Regarding ethnicity, a significant protective association was noted in European men and in Asian women. Decaffeinated coffee exhibited a protective effect in both men and women [ 53 ]. On the contrary, other researchers have found no protective evidence for coffee.…”
Section: Coffee and The Gastrointestinal Tract: Focus On The Mucosmentioning
confidence: 99%
“…In colorectal adenoma, coffee drinking is borderline protective [ 123 , 124 , 125 ]. For pancreas cancer, there is no association between coffee exposure and cancer risk [ 77 , 78 , 126 , 127 , 128 , 129 ].…”
Section: Impact Of Coffee On Cancer Risk In Humansmentioning
confidence: 99%
“…Both genetic and environmental factors play an important role in the etiology of this disease [10]. Large population studies with varying strength of evidence have found CRC-protective factors such as certain food groups (fruits and vegetables [11], fish [12]), specific foods (garlic [13] and coffee [14]) and dietary components (fiber, resistant starch, folate, vitamin B6, vitamin D, calcium and magnesium) [9,15]. In addition, physical activity (PA) [16] and certain drugs (aspirin, non-steroidal anti-inflammatory drugs [17] and hormonal replacement therapy (HRT) in postmenopause [18]) could decrease the CRC risk.…”
Section: Introductionmentioning
confidence: 99%